2006
DOI: 10.1128/aac.00238-06
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Ceftobiprole and Other β-Lactams against Streptococcus pneumoniae Clinical Isolates from the United States with Defined Substitutions in Penicillin-Binding Proteins PBP 1a, PBP 2b, and PBP 2x

Abstract: The activities of ceftobiprole and other ␤-lactams were examined with 30 Streptococcus pneumoniae isolates containing multiple pbp1a, pbp2b, and pbp2x mutations. The highest ceftobiprole MIC was 1 g/ml, while the comparator MICs were 16 to 64 g/ml. Fifty percent inhibitory concentrations for penicillin-binding protein 2x were 0.5 g/ml (ceftobiprole) and 4 g/ml (ceftriaxone) in a penicillin-and ceftriaxone-resistant isolate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…A distinguishing feature of ceftobiprole is that, in addition to inhibiting the normal complement of PBPs in most species, it also binds with a high affinity to the acquired PBP 2a (PBP 2Ј) of MRSA strains, PBP 2a of Staphylococcus epidermidis, and PBP 2x of penicillin-resistant Streptococcus pneumoniae (14,17,22,26). Ceftobiprole does not bind to PBP 5 of Enterococcus faecium and therefore has high MICs when it is tested with this organism (17).…”
mentioning
confidence: 99%
“…A distinguishing feature of ceftobiprole is that, in addition to inhibiting the normal complement of PBPs in most species, it also binds with a high affinity to the acquired PBP 2a (PBP 2Ј) of MRSA strains, PBP 2a of Staphylococcus epidermidis, and PBP 2x of penicillin-resistant Streptococcus pneumoniae (14,17,22,26). Ceftobiprole does not bind to PBP 5 of Enterococcus faecium and therefore has high MICs when it is tested with this organism (17).…”
mentioning
confidence: 99%
“…Previous studies from this laboratory have shown that ceftobiprole maintained activity against penicillin-and ceftriaxone-resistant S. pneumoniae strains that contained multiple mutations in PBP genes and that ceftobiprole had affinity for the primary cephalosporin targets PBP 1a and PBP 2x in both penicillinsusceptible and -resistant isolates (4,5). Surprisingly, in a penicillin-susceptible isolate, ceftobiprole had measurable PBP 2b affinity (4), which is not a primary target for previously characterized cephalosporins (8).…”
Section: ␤-Lactam Resistance Inmentioning
confidence: 99%
“…Altered PBP 1a, PBP 2x, and PBP 2b are the most important PBPs for ␤-lactam resistance among clinical isolates (5,6,8). Cephalosporins have the highest affinity for PBP 1a and PBP 2x, with no appreciable affinity for PBP 2b, while penicillins have high affinity for all three PBPs in penicillin-susceptible strains (6,8).…”
mentioning
confidence: 99%
“…It has been described that beta-lactam MIC values correlated closely with increases in the numbers of PBP1a, PBP2x and PBP2b substitutions. 30 Alpha-and beta-hemolytic streptococci have been shown to have low ceftobiprole MICs in several studies. 15,20,21 Penicillin-susceptible, -intermediate and -resistant isolates of S. pneumoniae are highly susceptible to ceftobiprole in vitro.…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%